A prospective cohort study on incidence of “opportunistic infections” among HIV infected ART naïve rural people of Kanchipuram district - Kasthuri, A.; Mohana Krishnan, K.; ., Amsavathani (International Journal Of Community Medicine And Public Health, 2018)
Background: In HIV-infected patients, progressive decline in their immunological response makes them susceptible to variety of common and opportunistic infections. Methods: This study was designed as a prospective cohort study and was done at the Meenakshi Medical College & Research institute, an academic and Tertiary medical centre in Kanchipuram, Tamil Nadu, South India. The study duration was from June 2004 to June 2010. The study was approved by the institutional review board of MAHER University, Chennai. The study population was drawn from the population of newly diagnosed HIV infected ART naïve rural people receiving care at the hospital. Results: In this study, from June 2004 to June 2010, faecal specimens were collected from a total of 207 HIV reactive patients and 20 controls. Of the total reactive patients, the following number of patients were present with the intestinal opportunistic infections like cryptosporodiosis 31 (15%), isosporiasis 13 (6.3%), cyclosporiasis 2 (1%), strongyloidiasis 8 (3.9%) and microsporodiosis 1 (0.5%). also, some of the other opportunistic infection were found during routine screening like candidiasis 32 (15.5%), toxoplasma infection 5 (2.4%), herpes infection 7 (3.4%) and CMV 5 (2.4%) (p=0.01). All the controls who had been tested for the above parasitic infections showed negative results. There were 42 (20.3%) patients diagnosed with pulmonary tuberculosis and 12 (5.2%) cases were diagnosed with extra pulmonary tuberculosis (p=0.01). Conclusions: Among the incidence of opportunistic infections, intestinal parasites and TB are more common among HIV infected ART naïve patients is significantly high than the controls.